A comparison of freshwater mussel assemblages along a land‐use gradient in Minnesota. Issue 11 (21st July 2019) - Hornbach, Daniel J.; Hove, Mark C.; MacGregor, Kelly R.; Kozarek, Jessica L.; Sietman, Bernard E.; Davis, Mike
Abstract: Intensive agricultural land use may have adverse impacts on freshwater mussel assemblages. Before European settlement, the Minnesota River Basin (MRB) was home to dense and diverse assemblages of freshwater mussels. Of the 40 species that occurred there, 43% have been extirpated. the St. Croix Basin (SCB) in Minnesota/Wisconsin, in contrast, has maintained a dense and diverse mussel assemblage, probably owing to the maintenance of a higher‐quality ecosystem. Mussels were sampled in four rivers representing an agricultural land‐use gradient. Timed searches were conducted in each of three rivers of the MRB, and in one river in the SCB in 2015. These were previously sampled by the Minnesota Department of Natural Resources (1998–2008). Mussel abundance and richness were lower in the MRB compared with the SCB. There were negligible changes in mussel density in the SCB, whereas abundances declined 17–83% in the MRB over the same period. Rates of decline were greatest for rivers with higher agricultural land use. Individuals of species that inhabited both basins were larger in tributaries with higher agricultural land use. MRB rivers with increased agricultural land use harboured a greater proportion of individuals displaying opportunistic (low life‐span, age and high fecundity) and periodic life‐history traits (moderate to high growth rates, low to intermediate fecundity, life span and age at maturity), whereas SCB assemblages had a greater percentage of mussels displaying equilibrium life‐history traits (long life‐span, late maturity and low reproductive effort). Also, rivers with higher amounts of suspended sediment contained more individuals classified as disturbance tolerant. This study provides evidence that agricultural land use contributes to the loss of mussel diversity and abundance, especially in mussel species that are long lived or slow to reproduce. These life‐history traits may be correlated with increased sensitivity to disturbances commonly observed in agricultural basins, including more and larger flood events.